Penerapan Akuntansi Manajerial dalam Menghadapi Tantangan Lingkungan Bisnis pada Perusahaan DANONE Indonesia - Yolanda Simanjuntak; Klaudia S Manik; Lasmaria Pasaribu; Lisnawati Lase; Hamonangan Siallagan (Pusat Riset dan Inovasi Nasional, 2025)
Danone, as one of the leading companies in the global food and beverage sector, faces significant environmental challenges, particularly regarding plastic pollution and exploitation of water resources. This study aims to explore the role and effectiveness of managerial accounting in helping the company address these challenges. Utilizing a literature review method, this study analyzes how managerial accounting can provide relevant information for planning, organizing, controlling and decision-making. The findings show that managerial accounting contributes to the identification and measurement of environmental performance. In addition, managerial accounting plays a role in product pricing that considers environmental costs and assessing environmentally friendly projects. To improve environmental performance, it is recommended that Danone improve more environmentally friendly technologies. This study offers insights into the importance of managerial accounting in supporting sustainability and corporate social responsibility in the global era